15 Stimulating the brain with sound: focused ultrasound for neuromodulation. Issue 8 (20th July 2020) - Butler, Chris
Abstract : Chris Butler studied medicine at Gonville and Caius College, Cambridge (1991–1994) and then at the University of Edinburgh (1994–1997). He conducted his PhD on the syndrome of transient epileptic amnesia under the supervision of Professor Adam Zeman. He worked as a post-doctoral fellow at the Memory and Aging Center, University of California at San Francisco and moved to Oxford in 2009. He was awarded a Clinician Scientist fellowship from the Medical Research Council in 2013. Transcranial ultrasound stimulation (TUS) is emerging as a potentially powerful, non-invasive technique for focal brain stimulation. TUS uses low intensity focused ultrasound delivered through the skull to cause direct modulation of neuronal function. In animal studies, TUS has been shown to modulate activity in several brain areas, including sensorimotor regions, visual cortex, frontal eye fields, anterior cingulate cortex and thalamic targets, resulting in behavioural as well as electrophysiological changes. Several studies have shown that TUS can be applied safely to healthy human participants to modulate behaviour and neural activity in brain regions including somatosensory, visual, and motor cortex as well as to deeper thalamic nuclei. These data have resulted in TUS emerging as a safe, potent, non-invasive brain stimulation tool, with better spatial accuracy and greater depth than established techniques such as transcranial magnetic or electrical stimulation. I will review these studies and discuss recent work of our own in which we studied, for the first time, TUS effects on higher-order human cortex. We investigated whether TUS can modulate higher-order visual processing both in superficial (middle temporal area (MT)) and deep (fusiform face area (FFA)) regions. Magnetic resonance imaging was used to map skull anatomy and functional regions of interest (MT and FFA) for each participant (n=16). To control for non-specific effects, auditory masking was applied during the tasks. EEG data were collected throughout. Auditory masking reduced subjective stimulation detection to chance level and abolished auditory evoked potentials. Ultrasonic stimulation of MT led to facilitation of visual motion detection in the contralateral hemifield, with no effect upon face identity detection. Stimulation of FFA did not affect visual motion detection performance. We show that TUS can be used in humans to modify behaviour and electrophysiological activity in higher-order visual pathways in a task- specific and anatomically precise manner.